2017
DOI: 10.20964/2017.03.21
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion of Copper in a Concentrated LiNO3 Solution at a High Temperature

Abstract: This paper presents the effects of the concentration, temperature, pH and Li 2 CrO 4 on copper corrosion in a concentrated LiNO 3 solution. The LiNO 3 concentration had opposite effects on the copper corrosion. The corrosion rate increased with increasing temperatures, but decreased with increasing pH levels. Below 220 °C, Li 2 CrO 4 promoted the formation of a thin and compact passive film comprising CuO, Cu 2 O and Cr 2 O 3 , which effectively inhibited the copper corrosion. Regarding corrosivity, the maximu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 47 publications
0
8
0
Order By: Relevance
“…Figure 2(a) shows that copper immersed in S 1 solution got the more active potential during the first seconds (from 0 to 1000 s) with a E OCP of −310 ± 16 mV, decreasing gradually until −320 ± 10 mV. In the presence of LiNO 3 (S 2 solution), E OCP of copper is displaced to less active potentials, registering a value of −245 ± 14 mV shifted throughout the time toward more active potential (−263 ± 9 mV), suggesting the formation of a layer of corrosion products, compounded by CuO and Cu 2 O [1416] due to the presence of normalNnormalO3 [17] and copper oxidation in Cu + and Cu −2 ion promoting due that the normalNnormalO3act as a cathodic reagent that produces normalNnormalO2 via: Then the NO2 is converted into nitrous oxide and oxygen ions as it was described by Rizvi et al as follows [18]: The latter allowed the formation of a stable passive film of CuO and Cu(OH) 2 .
Figure 2 OCP behaviour for the copper immersed in S 1 , S 2 , S3 and S 4 solutions at 25, 50 and 80°C.
…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Figure 2(a) shows that copper immersed in S 1 solution got the more active potential during the first seconds (from 0 to 1000 s) with a E OCP of −310 ± 16 mV, decreasing gradually until −320 ± 10 mV. In the presence of LiNO 3 (S 2 solution), E OCP of copper is displaced to less active potentials, registering a value of −245 ± 14 mV shifted throughout the time toward more active potential (−263 ± 9 mV), suggesting the formation of a layer of corrosion products, compounded by CuO and Cu 2 O [1416] due to the presence of normalNnormalO3 [17] and copper oxidation in Cu + and Cu −2 ion promoting due that the normalNnormalO3act as a cathodic reagent that produces normalNnormalO2 via: Then the NO2 is converted into nitrous oxide and oxygen ions as it was described by Rizvi et al as follows [18]: The latter allowed the formation of a stable passive film of CuO and Cu(OH) 2 .
Figure 2 OCP behaviour for the copper immersed in S 1 , S 2 , S3 and S 4 solutions at 25, 50 and 80°C.
…”
Section: Resultsmentioning
confidence: 99%
“…Subsequently, to achieve a more uniform surface, the samples were ground prior to every electrochemical analysis. Four electrolytic solutions were established to evaluate the corrosion effect of the copper immersed in lithium bromide water solution combined with other refrigerant absorbents, the concentrations used were based on the reported by [14] (Table 1).…”
Section: Experimental Methodologymentioning
confidence: 99%
See 1 more Smart Citation
“…Because the steel surface is exposed to air and moisture, the iron in the surface undergoes electrochemical reactions to produce Fe(OH) 2. This will then be further oxidized to Fe2O3 and Fe3O4, and α-FeOOH [25]. After surface preparation, Fe2O3 and Fe3O4 immediately form a thin film on the carbon steel surface which was seen in the obtained XRD pattern.…”
Section: Xrd Analysis Of Carbon Steelmentioning
confidence: 90%
“…It has been shown that in water/lithium bromide absorption heat pump systems, corrosion can be a problem especially in the high‐temperature regions of the system and therefore, a careful choice of materials is needed . With common materials such as carbon and stainless steel, ammonia/lithium nitrate solutions have reasonably low corrosion rates at temperatures of up to 150°C …”
Section: Discussionmentioning
confidence: 99%